Nothing about Us without Us in Precision Medicine: A Call to Reframe Disability Difference in Genetics and Genomics - Mintz, Kevin (The Hastings Center report, 2024)
Sixty-one million Americans and approximately a billion people worldwide live with some form of disability that limits one or more major life activities. The field of precision medicine continues to grapple with how to best serve disability communities. In this paper, we suggest that precision medicine faces an ethical tension between its goal to treat or cure disabling conditions and views that consider disability as a marginalized identity. We appeal to the concepts of recognition justice and distributive justice to argue that the ELSI community should take a more proactive role in promoting disability inclusion in precision medicine's practice and research. We also highlight two priorities for the ELSI community moving forward: facilitating greater collaboration between genetics and genomic professionals and disability communities and advocating for inclusive research design and disability accommodations in the research process.